(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
The Purpose of this research are to identify the role of Ana’dara Kallolo Soppeng as a tourism ambassador in promoting tourist attractions in Soppeng Regency and to find out the supporting and inhibiting factors for Ana’dara Kallolo in promoting tourism in Soppeng Regency. This research used a qualitative method to investigate more deeply the focus that observed carefully. The purpose of this study is to describe how the communication strategy used by Ana’dara Kallolo in promoting tourist attractions in Soppeng Regency and to understand the supporting and inhibiting factors of tourism ambassadors in promoting tourism in Soppeng Regency. The results of this research showed that Ana’dara Kallolo as the executor of the activity, Ana’dara Kallolo as a tourism information center, Ana’dara Kallolo as the Soppeng Regency Tourism Ambassador. and the supporting factors show the high public interest in tourism places in Soppeng district, the inhibiting factor is the lack of community resources when tourism promotion is carried out.